Cyril and Methodius. Historical Milieu and Usage of the Holy Scripture in Their Mission among the Slavs - Koundouris, Georgios (Forum Theologicum Sardicense, 2025)
Georgios Koundouris, Cyril and Methodius. Historical Milieu and Usage of the Holy Scripture in Their Mission among the Slavs The current paper examines the mission of Cyril and Methodius and their theological approach to the Holy Scriptures. It considers the historical context and key figures associated with the Byzantine mission among the Slavs in Central Europe. The specific theological interpretations of Scriptural texts in their mission are deeply rooted in the exegetical tradition of the Greek Fathers and follow well-established patterns of Byzantine theological heritage.